Assessing the Needs of the Elderly in Integrated Health and Social Services in the Russian Federation - Selezneva, E. V. (World Bank, Moscow, 2020)
The populations of both developed and developing countries are aging, a trend that means that all countries need to pay particular attention to providing health and social care to the elderly. The aging of the population is one of the key global drivers for integration of care. The increasing incidence of chronic diseases and comorbidities requires more coordination across care providers and settings. Improving health and social services for elderly people is one of the priorities for the government of the Russian Federation. This report attempts to address that gap by presenting the results of a study conducted in three Russian regions to assess the needs of the elderly for integrated health and social services. The main objective of this study is to find out to what extent the national social and health care policies targeting the elderly meet their needs and consider their abilities.